An Overview of Vagal Paraganglioma Surgery: Evaluation of Operative Morbidities and Quality of Life After Surgery - Ünsaler, Selin; Kılıç, Halime; Şen, Cömert; Başaran, Bora (ENT Updates, 2021)
Objective: To analyze postoperative morbidity and quality of life of surgically treated patients for vagal paraganglioma. Methods: Preoperative symptoms and findings, presence of cranial nerve paralysis, radiological findings, surgical techniques, perioperative, and postoperative complications were analyzed retrospectively. Washington University Quality of Life Questionnaire (UW-QOL) was used to evaluate the quality of life of the patients. Results: Of the 11 patients, 8 were women and 3 were men with an age distribution of 22-70 (mean age, 49.9 years). Two patients had vocal cord paralysis and 1 patient had hypoglossal nerve paresis preoperatively. In 5 patients, the vagus nerve was partially resected; vocal cord movements recovered within 6 months in 2 out of 5 (40%). Thecontinuity of the nerve could not be preserved in the remaining 6 patients, Ishiki type 1 medialization thyroplasty was performed in 4 (44.4%). In 3 patients, the hypoglossalnerve was invaded by the tumor and was sacrificed. Temporary facial paresis occurred in 3 patients who were operated on with transcervical-transparotid approach. Complete recovery was achieved in all within 3 months. In a patient with an extensively large tumor, carotid bypass surgery was performed with the saphenous vein. Except for one patient, the mean scores of all patients were above 90 with UW-QOL. Conclusion: Surgery, which is the only curative treatment method, may not cause a significant change in the postoperative quality of life in well-selected cases. Trying to protect the vagus nerve by dissecting it as much as possible and rehabilitation with Isshiki type 1 thyroplasty in case of aspiration are key points.